Neutral Sphingomyelinase Behaviour in Hippocampus Neuroinflammation of MPTP-Induced Mouse Model of Parkinson's Disease and in Embryonic Hippocampal Cells. (16th November 2017) - Cataldi, Samuela; Arcuri, Cataldo; Hunot, Stéphane; Légeron, François-Pierre; Mecca, Carmen; Garcia-Gil, Mercedes; Lazzarini, Andrea; Codini, Michela; Beccari, Tommaso; Tasegian, Anna; Fioretti, Bernard; Traina, Giovanna; et al.
Abstract : Neutral sphingomyelinase is known to be implicated in growth arrest, differentiation, proliferation, and apoptosis. Although previous studies have reported the involvement of neutral sphingomyelinase in hippocampus physiopathology, its behavior in the hippocampus during Parkinson's disease remains undetected. In this study, we show an upregulation of inducible nitric oxide synthase and a downregulation of neutral sphingomyelinase in the hippocampus of 1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine- (MPTP-) induced mouse model of Parkinson's disease. Moreover, the stimulation of neutral sphingomyelinase activity with vitamin 1, 25-dihydroxyvitamin D3 reduces specifically saturated fatty acid sphingomyelin by making sphingomyelin a less rigid molecule that might influence neurite plasticity. The possible biological relevance of the increase of neutral sphingomyelinase in Parkinson's disease is discussed.